The Urgency of Gender Equality in Indonesian Customary Inheritance Law: Review and Comparison with Other Countries - FARAH NIZRINA AULIA; Rato, Dominikus; Ochtorina Susanti, Dyah (Veteran Law Review, 2025)
The kinship system used in Indonesia, especially in customary inheritance law, is considered to have the potential to result in gender inequality because the distribution of inheritance given is considered unfair, especially implemented in the modern era like now. Therefore, the purpose of this study is to analyze the application of inheritance law in Indonesia and examine the views of customary inheritance law on gender equality, as well as a comparison of its application in other countries. The researcher used a normative legal method by conducting a literature review. The results of the study show that Indonesia applies patrilineal, matrilineal, and bilateral systems in the customary inheritance law kinship system. In practice, the patrilineal and matrilineal systems are considered less appropriate in terms of inheritance distribution because they use a system of drawing the father's or mother's lineage or can be said to be based on gender. If we look at the systems used by other countries, it seems that they are also inseparable from systems that end up ignoring gender equality.